IMPACT OF PROGRESSIVE SPEED TRAINING ON URBAN AND RURAL ADOLESCENT SCHOOL BOYS - Dr. A.Mahaboobjan (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of the study aims to identify the impact of progressive speed training basis on the duration of training of the urban and rural adolescent school boys. To achieve the purpose of the study forty (80) school boys were randomly selected as subjects from various places of urban and rural school boys from Salem District, Tamilnadu. Their age ranged between 14 to 17 years. They were divided into four equal groups such as experimental group I, experimental group II, control group I and control group II. These four groups were further divided into two experimental groups and two control groups and in each of the groups, there were 20 students. Initially, 4 weeks of uniform conditioning training was given to all groups before the pretest T1 was conducted. Further, consecutively 3 more post-tests (T2, T3, & T4) were conducted after every 4 weeks providing progressive speed training. In the descriptive part Mean trimming was revealed. For the comparison of performed Tests timing, MANOVA, ANOVA, and LSD post hock test were employed. The result of the study reveals that urban and rural adolescent school boys responded positively with the designed progressive speed training. This progression of sprint test timing took place progressively over time on the urban and rural boys distinctly within the groups. Progression of urban boys took place from Test 1 to Test 2 numerically but not statistically, which is the dissimilarity in the process of progression of speed ability with the urban boys. It is concluded that alike progressive speed training is equally effective for the urban and rural adolescent schoolboys but the progression of rural boys begins a bit slower in the early stages than the urban in the sprint ability.